Cream Formulation Of Methanol Extract Of Tapak Kuda Leaves (Ipomoea Pes Caprae (L.) R. Br.) As Anti-Inflammatory in Male White Mice (Mus Musculus) - Heldi Candra; Fifin Oktaviani; Andini Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The study entitled “Cream Formulation of Methanol Extract of Tapak Kuda (Ipomoea pes-caprae (L.) R. Br.) Leaves) As an anti-inflammatory in male white mice (Mus musculus)” using laboratory experimental methods with posttest control group design, data analysis using SPSS 25.0 with One Way ANOVA test and Duncan test. The percentage of extract yield obtained was 3.12%, phytochemical screening test showed the presence of secondary metabolite compounds alkaloids, terpenoids, flavonoids, saponins, tannins and steroids. Cream preparation of methanol extract of Tapak Kuda leaves at concentrations of 2.5%, 5% and 10% showed anti-inflammatory activity and the maximum dose to reduce edema diameter was 10% concentration with a percentage inhibition of 87.97%. Data analysis with One Way ANOVA test with a significance value ≤ 0.05 which indicates the presence of anti-inflammatory activity in Ipomoea pes-caprae tread leaf methanol extract cream.